The Intension of Students Entrepreneurship in State Polytechnic of Padang - Rusmadi, Rusmadi (AT-TALIM, 2014)
The objectives of this research were to identify the relationship between entrepreneur intention (Y) and information of entrepreneur intention (X1), model of parents guidance to entrepreneur intention (X2), and the attitude of entrepreneur cooperation to entrepreneur intention (X3) in them. Besides, the study also seeks the correlation between information of entrepreneur intention (X1), model of parentsâ guidance to entrepreneur intention (X2), and attitude of entrepreneur intention (X3). Questionnaires were used to investigate the model of parents guidance, and attitude of entrepreneur cooperation to entrepreneur intention. The result showed that there were significant linear regression of entrepreneur information to entrepreneur intention (26,7%) and significant linear correlation among variables that are information, model of parents guidance, and attitude of entrepreneur cooperation with entrepreneur intention (5,8%).